Diaphragm Structure and Function in Emphysematous Hamsters - WD Reid; RK Wilton (Canadian Respiratory Journal)
OBJECTIVE: To determine if muscle fibre injury, reduced force output and fatigue of the diaphragm accompanied hyperinflation induced by experimental emphysema.